(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2022)
This article proposes reflections on justice in the light of Paul Ricouer’s lessons. For this, it examines the culture of litigation in Brazil in opposition to the proposal of culture of peace, implemented by the United Nations and accepted by the National Judiciary, through Resolution nº 125/2010 of the National Coucil of Justice – CNJ, and, in the end, analyses the relationship between justice and peace.